Surface-enhanced infrared spectroscopy using resonant nanoantennas - Neubrech, Frank; Huck, Christian; Pucci, Annemarie (Chemical reviews, 2017)
Infrared spectroscopy is a powerful tool widely used in research and industry for a label-free and unambiguous identification of molecular species. Inconveniently, its application to spectroscopic analysis of minute amounts of materials, for example, in sensing applications, is hampered by the low infrared absorption cross-sections. Surface-enhanced infrared spectroscopy using resonant metal nanoantennas, or short “resonant SEIRA”, overcomes this limitation. Resonantly excited, such metal nanostructures feature collective oscillations of electrons (plasmons), providing huge electromagnetic fields on the nanometer scale. Infrared vibrations of molecules located in these fields are enhanced by orders of magnitude enabling a spectroscopic characterization with unprecedented sensitivity. In this Review, we introduce the concept of resonant SEIRA and discuss the underlying physics, particularly, the resonant coupling between molecular and antenna excitations as well as the spatial extent of the enhancement and its scaling with frequency. On the basis of these fundamentals, different routes to maximize the SEIRA enhancement are reviewed including the choice of nanostructures geometries, arrangements, and materials. Furthermore, first applications such as the detection of proteins, the monitoring of dynamic processes, and hyperspectral infrared chemical imaging are discussed, demonstrating the sensitivity and broad applicability of resonant SEIRA.
Gesehen am 23.04.2018